Answer:
Simplifying
12x2 + -13x + -4 = 0
Reorder the terms:
-4 + -13x + 12x2 = 0
Solving
-4 + -13x + 12x2 = 0
Solving for variable 'x'.
Factor a trinomial.
(-1 + -4x)(4 + -3x) = 0
Subproblem 1
Set the factor '(-1 + -4x)' equal to zero and attempt to solve:
Simplifying
-1 + -4x = 0
Solving
-1 + -4x = 0
Move all terms containing x to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + -4x = 0 + 1
Combine like terms: -1 + 1 = 0
0 + -4x = 0 + 1
-4x = 0 + 1
Combine like terms: 0 + 1 = 1
-4x = 1
Divide each side by '-4'.
x = -0.25
Simplifying
x = -0.25
Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve:
Simplifying
4 + -3x = 0
Solving
4 + -3x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + -3x = 0 + -4
Combine like terms: 4 + -4 = 0
0 + -3x = 0 + -4
-3x = 0 + -4
Combine like terms: 0 + -4 = -4
-3x = -4
Divide each side by '-3'.
x = 1.333333333
Simplifying
x = 1.333333333
Solution
x = {-0.25, 1.333333333